Using a portable terahertz spectrometer to measure the optical properties of in vivo human skin - Echchgadda, Ibtissam; Grundt, Jessica A; Tarango, Melissa; Ibey, Bennett L; Tongue, Thomas; Liang, Min; Xin, Hao; Wilmink, Gerald J (Journal of biomedical optics, 2013)
Terahertz (THz) time-domain spectroscopy systems permit the measurement of a tissue's hydration level. This feature makes THz spectrometers excellent tools for the noninvasive assessment of skin; however, current systems are large, heavy and not ideal for clinical settings. We previously demonstrated that a portable, compact THz spectrometer permitted measurement of porcine skin optical properties that were comparable to those collected with conventional systems. In order to move toward human use of this system, the goal for this study was to measure the absorption coefficient (μa) and index of refraction (n) of human subjects in vivo. Spectra were collected from 0.1 to 2 THz, and measurements were made from skin at three sites: the palm, ventral and dorsal forearm. Additionally, we used a multiprobe adapter system to measure each subject's skin hydration levels, transepidermal water loss, and melanin concentration. Our results suggest that the measured optical properties varied considerably for skin tissues that exhibited dissimilar hydration levels. These data provide a framework for using compact THz spectrometers for clinical applications.